Multi-detector arrangements for on-line measurements of γ-ray and neutron multiplicities - Kerek, A.; Kihlgren, J.; Lindblad, Th.; Pomar , C.; Sztarkier, J.; Walus, W.; Skeppstedt, Ö.; Białkowski, J.; Kownacki, J.; Sujkowski, Z.; Zgliński, A. (Elsevier B.V., 1978)
Fil: Kerek, A. Research Institute of Physics; Suecia